FDI and Its Impact on Rural Development: Economic and Infrastructure Perspective - Dr. Reena, (The journal of contemporary issues in business and government, 2023)
FDI stimulated rate of economic growth at every step of development of a nation. Developing countries encounter both capital appreciation and transfer of technology with the help of FDI. Today economical progress is highly reliant on improving not just the arrangement of capital, but also approach to technological capabilities, infrastructure and resource of any nation. This has improving economic liberalization of most of developing countries. The role of MNC as a viable source of both technology and capital is one of the salient features of this new openness. FDI is that investment that is presents the commercial profits of investors of country that is a dissimilar country different from enterprise of home nation. An origin enterprise and its overseas subsidiary are to accesses to FDI (G. Panneerselvam, 2012). Objectives of the study are to study the opportunities available in Rural development and to study Impact of FDI on Rural Development specifically on Infrastructure and Economic variable. Sample size is 384. 800 Questionnaires were distributed. 600 questionnaires were received but 510 questionnaires are correctly filled by respondents. Sampling technique is Purposive and Convenience sampling. Statistical Tools are Mean, Rank, Percentage, Correlation and Multiple Regressions. There is positive correlation between FDI and Infrastructure Variable in rural area in Haryana State which means the impact of FDI inflow on Rural Development is statistically significant in case of Infrastructure Variable. There is positive correlation between FDI and Economic Variable in rural area in Haryana State. In this case the impact of FDI inflow on Rural Development is statistically significant in case of Economic Variable. The Government of Haryana advised that time to time the FDI Policy should be implemented /modified and New FDI Policy should be formulated according to the business environment so that the foreign investors should be attracted and more and more FDI will be done in rural area of Haryana State.